The role of the SADC Protocol on Trade in Services in regional integration - Swanepoel, L. B. (North-West University, 2018)
Trade in Services can be described as a transaction between a supplier and a consumer without any physical movement of goods across international borders. This, in itself, presents major economic growth possibilities in both regional and multilateral terms. Regional trade agreements, if drafted to suit the specific region's strengths, can promote Trade in Services and establish regional integration. The fact that Trade in Services and regional integration, throughout the Southern African Development Community (SADC) specifically, is moving forward at such a slow pace is due to the lack of political ambition and policy makers failing to emphasise the establishment of trade specific regulatory coherence among member states. Given policy’s impact on Trade in Services, regional trade agreements must be designed to address new and emerging issues that, not only haven't been taken up in previous trade agreements, but which is also region specific and focused enough to build on new standards found in other new trade agreements that will boost regional integration. SADC countries are still in process of establishing a regional services market and, as it currently stands, major development possibilities still exist. This study compares the Trans-Pacific Partnership (TPP) with SADC’s Protocol on Trade in Services (PTIS), with the goal to determine the principles that are necessary to establish a regional market for the integration of Trade in Services. It was found that the PTIS lacks such principles and that integration of services throughout the SADC region is highly unlikely if set forth in its current direction. The finding was that the establishment of regional integration of Trade in Services throughout SADC will have to start with regulatory coherence among its members.
Keywords: Modes of trade; Regional integration; Regulatory coherence; Trade in Services

Trade Openness and Financial Development in Sub Saharan Africa: The Role of Institutional Quality - Abeka, Mac Junior (University of Cape Coast, 2018)
The financial development of many Sub-Saharan African countries over the years has not been able to match up with other regions like the Middle East and North Africa, East Asia and Pacific, and Europe and central Asia (IMF, 2016). Trade openness has been argued in several empirical literature as a factor that could spur up the level of financial development, although the high levels of trade openness in Sub-Saharan Africa is not contributing much to the desired levels of financial development in Sub-Saharan Africa. However, there is an indication in literature that trade openness will be more relevant to financial development of economies that have a strong institutional quality. Thus, by using system General Method of Moment estimation technique, this study examined how institutional quality moderates the relationship between trade openness and financial development of Sub-Saharan African economies. The study found that institutional quality enhances the effect of trade openness on financial development of Sub-Saharan African economies. It is therefore recommended that, Sub-Saharan African economies should put in measures to strength their institutional quality so that the high levels of trade openness will better enhance financial development. Specifically, trade openness can better enhance financial development by improving government effectiveness, reducing corruption, enhancing regulatory quality, abiding by the rule of law, and allowing voice and accountability. As an extra benefit, the improvements in institutional quality on their own too will yield positive impact on financial development.

Cross border merger and shareholder's rights - Severino, Francesco (LUISS Guido Carli, 2018)
Historical context. Scope of application of cross border merger. A comparison of class rights with minority protection in cross border merger. The transposition of the cross border merger in the German law for an implementation.

An analysis of the effects of tax policy and tax abuse on the fulfilment of human rights in developing countries : the case of Zambia - Chigubu, Salome (University of Johannesburg, 2018)
Keywords: Droit fiscal; Pays en voie de développement; Politique fiscale; Tax; Zambie

The position of assets vested in a sham trust - Diedericks, C. A. (North-West University, 2018)
The concept of a sham trust has changed over the years. Presently it is defined as a perceived entity that is not entirely what it portrays to be. In addition, a sham is therefore regarded as invalid with a deceiving nature. A sham trust has the consequence that all the benefits and protection of assets are destroyed, seeing that no trust actually came into existence. Considering the above, for the purpose of the present study, only an inter vivos trust was evaluated and discussed in detail. The law of contract is considered to be the foundation of the principles for an inter vivos trust. Therefore, the law of contracts can be applied to solve problems presented by trusts. During the course of the present research, it became evident: in instances where a trust is declared a sham, the consequence is that the trust will be deemed void. There are instances where a sale agreement has been concluded prior to the discovery of the true nature of the trust, namely it being a sham. This raises the question on the legal position of assets vested in a sham trust. A further question arises about the consequences and whether the courts should set a guideline for such instances. From the findings it is evident that such a guideline is necessary. This would enable courts to determine the consequences of assets vested in a sham trust. There are various possibilities regarding consequences for assets vested in a sham trust. To determine the applicable consequence, the court should deal with each case individually based on the facts of that particular circumstances. This consequence could either entail that the assets should fall within the founder’s personal estate, or whether the concluded sale agreement should be deemed void. It is evident that the courts struggled with the distinction between a sham and alter ego trust, however, the case law referred to below gives more clarity in this regard. A proper formulation of the aspects of sham and alter ego trusts was provided in the cases of Van Zyl v Kaye1 and Van der Merwe v Hydraulics.2 The formulation of the two aspects in the above-mentioned cases was confirmed in the Supreme Court of Appeal judgement in the case of WT v KT.3 In the Khabola v Ralitabo,4 the court dealt with the typical example of the sham trust. In brief, the fact of the case were, that the parties had the intention to establish a partnership that was simulated to be a trust.
Keywords: Assets; Contract of sale; Intention; Law of contract; Legal position; Sham trust; Snook test; inter vivos trust

A comparative analysis of constructive dismissal in South Africa and within other international jurisdictions - Kader, Riaz (University of KwaZulu-Natal, 2018)
Abstract available in PDF.
Keywords: Constructive dismissal; Employee termination; Employees; Employers; Employment relationship; Termination of employment

Choice of law in international commercial contracts : a comparative study of Private International Law in Ghana and South Africa - Kwame, Essah (University of Johannesburg, 2018)

A comparative legal perspective on the impact of good or bad faith on the independence of documentary credits and demand guarantees - Lupton, Cayle Selwyn (University of Johannesburg, 2018)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

Modification of choice of law in the BRICS countries : the role of Article 2(3) of the Hague Principles on choice of law in international commercial contracts - Ndlovu, Docus Sanele (University of Johannesburg, 2018)
Each member state of the BRICS countries is different about the modalities and limitations of party autonomy in their field of Private International law. The principle of party autonomy allows parties to choose the law applicable to their contract and is meant to respect the choice of contracting parties. Since laws are not absolute, they need to change to the needs of a changing society. This can generate a problem in instances where contracting parties have already chosen a choice of law to govern their contract. The question is then whether the governing law of a contract that was previously chosen by the parties can be changed after that contract has been concluded. The scope of party autonomy extends to permitting parties to modify their chosen law in instances where it is necessary to do so, subject to limitations of a specific legal system and principles of conflict of laws. However, the legal rules of each BRICS countries differ in permitting parties to modify the chosen law. This minor dissertation analyses whether the principle of party autonomy is recognised in each member state of the BRICS countries and whether it extends to allow for modification of choice of law. It further asserts that the BRICS countries could plausibly refer to the rules and recommendations of Article 2(3) of the Hague Principles on Choice of Law in International Commercial Contracts to advance the wide acceptance of modification of choice of law. LL.M. (International Commercial Law)

The directors’ fiduciary duty to act in the best interests of the company: the possible developments of common law by statute and how they affect human rights - Nomadwayi, Bakhulule (University of KwaZulu-Natal, 2018)
This research traces the developments of the directors’ fiduciary duty to act in the best interests of the company and looks at how these developments affect human rights and interests of stakeholders. The main focus of the study is on the human rights impact of this duty. Initially, this duty was only regulated in terms of common law which proved to be problematic. The problem with common law lies within the definition of ‘best interests of the company’, which not only exclude the interests of other stakeholders but also has the potential to bring about violation of human rights, particularly the rights to equality, dignity and fair labour practice. At common law best interests of the company means interests of the company itself and its shareholders. The common law only protects the company and its shareholders, while excluding the rights and interests of stakeholders. The common law duty to in the best interests of the company is not in line with our contemporary law because it ignores human rights. The neglect of human rights by this duty renders it inconsistent with the values contained in the Constitution. Furthermore, the exclusion of stakeholders’ rights by this duty cannot be justified because stakeholders play an important part in safeguarding the stability and continued existence of the companies. The fiduciary duty to act in company’s best interests is now contained in the Companies Act of 2008. Inclusion of this duty in the Act enables our courts to interpret it in a manner that protects human rights and which takes into account interests of other stakeholders. Section 7 (a) of the Act provides that among other goals of the Act is the promotion of compliance with the Bill of Rights when applying the company law. The impact of section 7 is that it imposes an indirect duty on directors to consider the human rights impact of their decisions. Section 158 of the Act enables the courts to “develop common law as it is necessary to improve the realisation and enjoyment of rights established by the Companies Act of 2008.” Given this recognition of the Bill of Rights by the Companies Act, it’s of vital importance that our courts should interpret and apply the duty to act in the best interests of the company in manner that is consistent with the Constitution. Directors are now obliged to pay attention to the human rights impact of their decisions.
Keywords: Best interests of the company; CSR; Corporate Social Responsibility; Fiduciary duty

Reckless and fraudulent trading by a company and the business judgment rule as a defence for directors - Peter, Lunga Cosmo (University of KwaZulu-Natal, 2018)
Abstract available in pdf.
Keywords: Business judgment rule; Company directors; Corporate governance; Fiduciary duties; Fraudulent trading; Good faith; Personal liability

Analysing and comparing the impact of misrepresentation and non-disclosure on the validity of a contract: similarities, differences and remedies - Ramphal, Kayra (University of KwaZulu-Natal, 2018)
This dissertation explores the concepts of non-disclosure and misrepresentation in South African law. The principal focus surrounds the effect non-disclosure as a form of misrepresentation has on the liability of contracting parties. In order to explore this effectively, the study explores the concept of duty of disclosure, and whether such a duty exists in South African law. Instances when a duty to disclose arises are explained, such as positive steps taken to conceal facts, the seller having sole knowledge of the material fact, an omission or misleading language, and a change in circumstances. Similarly to the English law duty of disclosure in relation to information in contracts uberrimae fidei, the similar South African law concept in insurance or agency contracts known as ‘utmost good faith’, is discussed and explored. The study determines whether such a concept should be a mandatory requirement in pre-contractual negotiations. Additionally, this study explores the various avenues of relief that are available to those who have fallen victim to misrepresentation. This results in an analysis of the effectiveness and success of the current traditional methods of claiming and quantifying damages that are adopted by South African legislature and the judiciary. The discussion then explores the proposed alternate method which aims to combine a claim into one of delict and that of contractual liability, or on the other hand institute a claim solely based on contractual liability. Lastly, this study explores the effect the Consumer Protection Act 68 of 2008 has had on contractual agreements, remedies and penalties, and how this ground-breaking legislation has altered the approach previously adopted by the common law and whether it has done enough to protect consumers.
Keywords: Contracting parties; Contracts; Duty to disclose; Liability; Misrepresentation; Non-disclosure

The interconnection between express choice of forum and tacit choice of law. A comparative analysis between common-law and civil-law jurisdictions - Roux, Keegan (University of Johannesburg, 2018)
Keywords: Commercial law; Conflict of laws; Contracts (International law)

The link between reckless credit and emolument attachment orders - Singh, Nishtha (University of KwaZulu-Natal, 2018)
South Africa has experienced significant levels of reckless credit thus leading to over-indebtedness of consumers. Furthermore, research conducted in 2008 and 2013 by the University of Pretoria indicated that there were abuses prevalent in emolument attachment orders (EAOs). An interesting aspect of the research was that credit providers were particularly interested in employed consumers, as their wages or salaries were deemed to be a form of security. The aim of this dissertation is to examine the link between reckless credit and EAOs. The main research problem revolves around the fact that credit providers do not conduct thorough pre-agreement assessments and have a tendency to subscribe to the tick box approach to compliance. Moreover, these pre-agreement assessments do not make provision for the inclusion of external market factors, which is essential to safeguard consumers against economic events. This dissertation argues that, at the point when reckless credit is granted, it is inevitable that default will occur thus leading to the culmination of an EAO. In this regard, the case of University of Stellenbosch Legal Aid Clinic and Others v Minister of Justice and Correctional Services and Others; Association of Debt Recovery Agents NPC v University of Stellenbosch Legal Aid Clinic and Others; Mavava Trading 279 (Pty) Ltd and Others v University of Stellenbosch Legal Aid Clinic and Others (CCT127/15) [2016] ZACC 32 is important. The judgement illustrates how vulnerable consumers fell prey to unscrupulous credit providers who then took advantage of their salaries. An important aspect about the judgement was that section 65J of the Magistrates Court Act has now been amended through a joint interpretative mechanism of severance and reading in. The Constitutional Court’s order now requires judicial supervision in the EAO process, whereby a magistrate issues the EAO. This dissertation examines the effect of this and how EAOs are currently regulated. It also discusses whether judicial supervision is the solution to ameliorating the law on EAOs. Qualitative research methods were utilised such as legislation, case law, textbooks and journal articles. While there are no statistics to prove the link, anecdotal evidence proves the link between reckless credit and EAOs.
Keywords: Credit market; Emolument Attachment Orders; Protection of Personal Information Act; Reckless Credit

Restraint of trade clauses: does the enforcement thereof promote anti-competitive behaviour in South African law? - Sithole, Mthokozisi Wesley Nhlakanipho (University of KwaZulu-Natal, 2018)
No abstract available.
Keywords: Anti-competitive behaviour; Business agreements; Competencia; Competition law; Employment agreements; Restraint of trade; Trade clause

A discussion of the success and failures of business rescue as a remedy for ailing companies - Sobantu, Vuyo (University of KwaZulu-Natal, 2018)
Companies are constantly facing risks, including financial constraints, which may contribute to companies being unable to trade in the manner desired. Unfortunately, companies that find themselves in this predicament have, in reality, been without a remedy from as early as statutory provisions regulating company law were promulgated in 1926. Judicial management, as a remedy, is notorious for being an outright failure, but the current Companies Act 71 of 2008 introduced the remedy of business rescue for financially distressed companies. The scrutiny and spotlight on the new remedy turns on whether it can be truly accessible for the companies in question and what significant changes it has made to favour financially distressed companies. This mini dissertation will aim to discuss whether the remedy of business rescue has been a success or failure.
Keywords: Ailing companies; Business rescue; Companies Act 61 of 1973; Companies Act 71 of 2008; Judicial management; South African company law; Winding up

A critical analysis on simulated transactions - Tshabalala, Alwanduxolo Thembalihle (University of KwaZulu-Natal, 2018)
No abstract provided.
Keywords: Simulated transactions; Tax avoidance; Tax evasion; Taxation

The effects of business rescue on the companies’ stakeholders : a comparative analysis between business rescue and judicial management - Xaba, Ntombikhona Thandeka (University of KwaZulu-Natal, 2018)
Upon the recognition that the implementation of the judicial management process would not be the success that it was anticipated it would be, it became apparent that there was need for a system of corporate rescue appropriate to the needs of a modern South African economy. The legislature then introduced a new business rescue regime when the Companies Act 71 of 20082 (the Act) came into effect in the South African law. This new Act remarkably changed corporate law. One of the central features of the Act is the introduction of business rescue- a procedure which provides for the rehabilitation of financially distressed companies in a manner that seeks to balance the rights of all stakeholders. These provisions are said to be the appropriate method for modern South African economy and they differently affect the stakeholders of a company. This thesis will be discussing the different rights given to affected persons in the new Companies Act and examine how the provisions of business rescue affect different stakeholders of the company and compare such effects with those experienced under judicial management, specifically in light of the improvements of the positions of the stakeholders. Although the new business rescue is a remarkable improvement from the old judicial management system, there is still room for improvement.
Keywords: Business rescue; Companies Act 71 of 2008; Company stakeholders; Judicial management; South African company law

A critical discussion of the directors’ duties and business judgement rule - Zondi, Sphesihle Brilliant (University of KwaZulu-Natal, 2018)
No abstract available.
Keywords: Companies Act 71 of 2008; Directors; Judgement rule; South Africa